Robustness Test of SIMON-32, SPECK-32, and SIMECK-32 Algorithms Using Fixed-Point Attacks. Issue 1 (March 2021) - Susanti, B H; Permana, O J; Amiruddin,
Abstract: SIMON-32 and SPECK-32 are a family of lightweight block ciphers publicly released by the National Security Agency (NSA) in June 2013. Meanwhile, SIMECK-32 is a lightweight block cipher based on the combination of good design components from SIMON- 32 and SPECK-32 block ciphers. In this paper, we tested the robustness of the SIMON-32, SPECK-32, and SIMECK-32 algorithms against fixed-point attacks. Block cipher fixed-points may facilitate fixed-point attacks if an adversary can control the block cipher key input. The results of fixed-point attacks on the SIMON-32, SPECK-32, and SIMECK-32 algorithms show that all three variants of the algorithm have fixed-points.